Herpetic Panophthalmitis: A Diagnostic Dilemma. (2nd January 2020) - Hassman, L. M.; Chung, M. M.; Gonzalez, M.; Bessette, A. P.
ABSTRACT: Purpose : To describe an uncommon presentation of ocular infection caused by human herpes simplex virus 2 (HSV-2). Methods : Case report. Results : A 32-year-old female with no prior history of mucocutaneous herpesvirus infection presented with a minimally painful hypertensive granulomatous panophthalmitis and optic neuropathy that was initially suspected to be orbital cellulitis. Her disease progressed despite antibiotic and steroid treatment, and HSV-2 was ultimately identified in the vitreous. Conclusion : Although rare, ocular infection by human herpesvirus can present as a panophthalmitis. The case is discussed in the context of two previously reported cases of herpes simplex panophthalmitis, as well panophthalmitis caused by varicella zoster virus.